Factors Affecting The Choice Of Payment Method In Modern Retail Shops - Maya Nur Annisaa; Nuryasman MN; Ira Geraldina (Jurnal Ekonomi, 2023)
Digitalization affects almost all areas of life, including payment methods. Now, there are many different payment methods. However, on the other hand, Indonesia's financial inclusion level still needs to catch up compared to neighboring countries. This study aims to determine the factors influencing the choice of payment method at minimarkets in Bekasi City by using transaction value, income, education, awareness ease of use, and awareness of risk as independent variables. Research data collection was carried out by distributing questionnaires to 400 respondents. The sampling method used a convenient regional random sample selection technique. Data collection found that electronic wallets are the most used payment method. Using the PLS-SEM method, the results found that transaction value, income, education, awareness ease of use, and awareness of risk have positive and significant impacts in increasing the likelihood of consumer’s behavior in choosing an electronic payment method.